2020
DOI: 10.1093/toxsci/kfaa168
|View full text |Cite
|
Sign up to set email alerts
|

Acute and Subacute Oral Toxicity of Deoxynivalenol Exposure in aDermatophagoides farinae-Induced Murine Asthma Model

Abstract: Previously, researchers have demonstrated that mycotoxin deoxynivalenol significantly enhances immunocyte activation. However, the interaction between deoxynivalenol exposure and immune disorders remains unclear. In this study, we aimed to investigate whether acute and subacute oral exposure to deoxynivalenol exacerbates the development of respiratory allergy using a mite allergen (Dermatophagoides farina, Derf)-induced mouse model of asthma. The direct relationship between deoxynivalenol exposure and asthma d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…In a mouse model of house dust mite -induced allergic asthma, acute and subacute oral treatment with DON significantly enhanced the inflammatory responses, by increasing the infiltration of CD3 + CD4 + helper T cells and IgE + B cells and enhancing production of IL-4, IL-5 and IL-13 in local lymph nodes (42). In the current study, there was no significant difference in the population of splenic Th2 cells between different groups, and the production of Th2-mediated cytokines, such as IL-13 and IL-4, from re-stimulated splenocytes of OVA-sensitized animals born to control and DON-exposed mothers was not significantly different.…”
Section: Discussionmentioning
confidence: 98%
“…In a mouse model of house dust mite -induced allergic asthma, acute and subacute oral treatment with DON significantly enhanced the inflammatory responses, by increasing the infiltration of CD3 + CD4 + helper T cells and IgE + B cells and enhancing production of IL-4, IL-5 and IL-13 in local lymph nodes (42). In the current study, there was no significant difference in the population of splenic Th2 cells between different groups, and the production of Th2-mediated cytokines, such as IL-13 and IL-4, from re-stimulated splenocytes of OVA-sensitized animals born to control and DON-exposed mothers was not significantly different.…”
Section: Discussionmentioning
confidence: 98%
“…An epidemiological study in 2013 (Parisi et al, 2013) indicated that the incidence of psoriasis is 2%–4% of the population in the United States and Europe but is lower in Asian countries; however, psoriasis is increasing in Japan due to a westernization of the population's diet (Yamashita et al, 2019). Our group is focusing on studying the relationship between development of allergic disease and mycotoxin exposure (Aihara et al, 2020; Ookawara et al, 2021). The present study aims to examine the relationship between oral exposure to actual contamination level of citrinin, which is known to highly contaminate red yeast supplement and the development of psoriasis.…”
Section: Discussionmentioning
confidence: 99%
“…We previously investigated the relationship between oral exposure to mycotoxin deoxynivalenol and the development of allergic diseases including atopic dermatitis and asthma, and oral exposure to low concentration of deoxynivalenol significantly exacerbated the local inflammation in mice model and in vitro immune cells (Aihara et al, 2020; Ookawara et al, 2021). Our findings imply that some mycotoxins can directly influence the function of immunocytes such as T cell, dendritic cell, and B cell.…”
Section: Introductionmentioning
confidence: 99%
“…The chronic effect is correlated with immune system suppression caused by the inhibition of mitophagy [62]. Other effects of DON are damage to the respiratory system that can lead to asthma [63] and alteration in the expression of MAPK (mitogen-activated protein kinase) proteins that are involved in the control of cell apoptosis, differentiation, and cell growth [64]. Recent studies linked these effects to indirect damage caused by DON to mitochondria, which will ultimately lead to cell death [65].…”
Section: Deoxynivalenolmentioning
confidence: 99%